2016
DOI: 10.1371/journal.pgen.1006155
|View full text |Cite
|
Sign up to set email alerts
|

Complex Ancestries of Lager-Brewing Hybrids Were Shaped by Standing Variation in the Wild Yeast Saccharomyces eubayanus

Abstract: Lager-style beers constitute the vast majority of the beer market, and yet, the genetic origin of the yeast strains that brew them has been shrouded in mystery and controversy. Unlike ale-style beers, which are generally brewed with Saccharomyces cerevisiae, lagers are brewed at colder temperatures with allopolyploid hybrids of Saccharomyces eubayanus x S. cerevisiae. Since the discovery of S. eubayanus in 2011, additional strains have been isolated from South America, North America, Australasia, and Asia, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
188
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(210 citation statements)
references
References 58 publications
(94 reference statements)
20
188
1
1
Order By: Relevance
“…The Kr values between S. eubayanus and S. uvarum (0.073) obtained here are in agreement with previous findings and are similar to those of the most divergent P. rhodozyma strains. However, recent reports showed large intraspecific diversity (as high as 1 %) within both Saccharomyces species [26–28], so Kr values are prone to vary considerably, depending on the lineages used for comparison. The only Basidiomycota cases we could retrieve for comparison was that of the sister species Cryptococcus gattii and C. neoformans , which have Kr values 2-fold higher than P. rhodozyma (0.14); similarly, two varieties of C. neoformans (var.…”
Section: Resultsmentioning
confidence: 99%
“…The Kr values between S. eubayanus and S. uvarum (0.073) obtained here are in agreement with previous findings and are similar to those of the most divergent P. rhodozyma strains. However, recent reports showed large intraspecific diversity (as high as 1 %) within both Saccharomyces species [26–28], so Kr values are prone to vary considerably, depending on the lineages used for comparison. The only Basidiomycota cases we could retrieve for comparison was that of the sister species Cryptococcus gattii and C. neoformans , which have Kr values 2-fold higher than P. rhodozyma (0.14); similarly, two varieties of C. neoformans (var.…”
Section: Resultsmentioning
confidence: 99%
“…This seems to be due to a lack of maltotriose transporters (Hebly et al 2015; Baker et al 2015). However, so far, only one Patagonian isolate, the S. eubayanus type strain CBS12357, has been characterized in terms of maltotriose utilization (Gibson et al 2013; Hebly et al 2015) and newly found strains, e.g., Northern Hemisphere isolates from China and North America (Bing et al 2014; Peris et al 2016) and the New Zealand isolate (Gayevskiy and Goddard 2016) remain to be characterized. The two subgroups of the lager yeasts, Saaz and Frohberg, also differ in their sugar utilization characteristics.…”
Section: Hybrid Phenotypesmentioning
confidence: 99%
“…Since the original isolation of S. eubayanus in South America, there have been a number of isolations elsewhere, including from North America (Peris et al 2014, 2016), East Asia (Bing et al 2014), and New Zealand (Gayevskiy and Goddard 2015) but, interestingly, not as yet from Europe. Recent sequence analysis suggests that there may be a Northern Hemisphere, or “Holarctic,” group of related strains with a wide geographical distribution, comprised (so far) of certain strains found in Tibet and in North America (Peris et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations